Mental hygiene movement as a (r)evolutionary trend in public health in interwar Kaunas and Vilnius from 1918 to 1939 - Žalnora, Aistis; Miežutavičiūtė, Vitalija (Acta medica Lituanica, 2016)
Objective. The health care system of the interwar period is distinguished by its revolutionary attempts to overcome social diseases and social hardships in general. In the researches published after the Second World War, different and in some cases even contradicting ideas on mental hygiene and eugenics were mixed together and were associated – almost exclusively – with the Nazi’s racist ideology, totalitarian, or authoritarian regimes. The assessments of social-medical policy of the interwar period in the Baltic region also became rather one-sided. Felder’s recent study (1) gives the impression that changes in psychiatry in Lithuania were caused by the Nazi’s eugenics as a single agent. However, there were other factors. One of the most significant ones was the mental hygiene movement that will be discussed in this paper. Methods. In this research we used descriptive and comparative methods. Results. After the First World War, the problem of treatment of the mentally ill was a medical and a social issue that required a completely new approach both in Lithuania and in Vilnius. The most notable manifestation of such a new attitude in psychiatry was a mental hygiene movement. University scientists in Vilnius and Kaunas were discussing issues of mental hygiene. Conclusions. The mental hygiene movement of the early 20th century played an important role in the later development in psychiatry and medical sciences. The ideas published by the medical doctors in Kaunas and Vilnius were partly characteristic of the interwar period, although some of them went far ahead of their times.